Prevalence of Histopathologic Types of Gingival Lesions in the Iranian Population: A 22‐Year Retrospective Study - Nafiseh Shamloo; Mostafa Alam; Armin Khaleghi (Wiley, 2024)
ABSTRACT Objectives Gingiva is one of the supporting tissues around the teeth that can be affected by various neoplastic or nonneoplastic lesions. Previous studies have examined several types of gingival lesions, but the lack of a standardized classification system has hindered meaningful comparisons. Additionally, many studies focused primarily on reactive lesions. Our study aims to contribute to the understanding of gingival lesions by investigating their prevalence across age groups, genders, sites, and by their clinical presentation. This research could lead to improved diagnostic accuracy and treatment strategies. Materials and Methods This retrospective study explores the prevalence of gingival lesions based on biopsies during a 22‐year span. The patient's demographic details, including age, gender, and lesion's clinical presentation were systematically collected. These lesions were categorized into six groups. Descriptive statistics, χ2 test of independence, and one‐way ANOVA were used for data analysis. Results Among the 7668 biopsied lesions, 684 (8.9%) lesions were located in the gingiva, with a greater occurrence in women (63.5%). Soft tissue tumors represented the most prevalent group in the gingival lesions (72.1%), and peripheral giant cell granuloma (PGCG) was the most frequent lesion (21.2%), followed by, pyogenic granuloma (19.3%), peripheral ossifying fibroma (17.8%) and focal fibrous hyperplasia (7.6%); all of which predominantly affected women, with mean ages falling in the fourth decade of life. Squamous cell carcinoma was recognized as the most common malignancy. Conclusion In this study, PGCG was found to be the most common lesion in the gingiva in Iranian population. Further analysis using a unanimous categorization is required to confirm these results.